Drawing lessons from a pluridisciplinary approach associating stakeholders for a better management of a bivalve population (French Atlantic coast)?. (5th April 2021) - Caill-Milly, Nathalie; Sanchez, Florence; Lissardy, Muriel; de Montaudouin, Xavier; Bru, Noëlle; Kermorvant, Claire; Ganthy, Florian
Abstract: Initially introduced for aquaculture purposes in the 70's on French territory, Manila clam ( Ruditapes philippinarum ) is now a neonatural resource within Arcachon Bay (SW of France). Its exploitation by professional fishermen represents around 300–450 tons per year and involves around 60–70 licenses depending on the year. The management of this species relies on both European and regional scale decisions. In 2000, a partnership between professionals and scientists was established in order to implement a sustainable management of this resource. Since then, a co-organized biannual survey has been performed to assess clam stock. Working groups and research programs were concomitantly developed. Initially stakeholders requested this survey only to assess clam stock in the bay. Nowadays, an integrative approach of the population functioning is privileged. Such approach is particularly relevant for population with high spatial and temporal distribution variations. The main considered drivers are diseases including constant infection by Perkinsus but also the discovery of a recently described pathology - BMD (Brown Muscle Disease), other environmental factors (i.e. trophic resources, hydrodynamic conditions, temperature …) and professional fisheries. Alternatively to classical stratified random sampling, the survey method is currently improved to optimize the sustainable management of this resource. New spatially balanced sampling design showed promising results increasing the efficiency of this survey. Knowledge is mobilized not only to meet the needs for expertise expressed locally but also at the national level. This paper aims to introduce how the different disciplines are combined to understand the dynamics of Manila clam population within its environment and how stakeholders are involved to ensure its sustainability and to improve management between users. Successes and failures are identified, as well as the points of improvement for future actions. Highlights: Benefit of co-management process, where definition of roles is essential, is highlighted. Difficulties are listed, including obtaining available funds to plan regular surveys. Integrative approach is relevant to sustain Manila clam population in Arcachon Bay. Complementary expertise and research actions made the collaborative process effective.